INFLUENCE OF CONFECTIONERY PRODUCT DECORATION ON CONSUMERS - Čugalj, Milana; Ivanović, Velibor; Kalenjuk Pivarski, Bojana; Bikić, Saveta (The Business of Tourism, 2024)
Confectionery has always been considered an art form. From the original form to what it is considered to be today, a long development period preceded, and the desserts transformed into real work of art. The appearance of a prepared and served dish is one of the most important factors of its attractiveness on the market. Also, it is considered to be one of the main motivators when making a decision about their purchase. In fact, consumers who have expectations related to a certain product must be stimulated by sensory characteristics, the first of which is the appearance. The first data on the decoration of sweets dates back to ancient Rome, and the techniques and means of decoration have been shaped and continue to be adapted to the needs of the market. Today, there are many different techniques used in decorating sweets, and the pastry chef must be precise and concise in portaying his emotions to the finished product, through the decoration. Consumers are guided by primal instincts and choose simpler, more reduced decorations that follow the taste of the confection with their appearance. The objective of the research is to analiyze the impact of the confectionary decoration on consumer behavior. The aim of the work is to obtain information about the importance of theof the pastry product decoration on consumers through consumer surveys. The research was conducted by surveying consumers in A.P. Vojvodina (R.Serbia), and the collected data was processed using descriptive statistics.
Keywords: confectionery; decoration; food prezentation; desserts; gastronomy aesthetics; consumer decision